Manajemen Pelayanan: Sebuah Perspektif Pelayanan Mahasiswa - Candra Sinuraya (Universitas Kristen Maranatha, 2010)
Having the management of ministry (students' ministry) is not simple; because it's concerning the subject are the college students who haven't many experiences. On the other hand, every year the students who manage this ministry are always changing. This article aims to give insights to people who concern in the student's ministry, such as adviser and the management of students' ministry, in order to have knowledge concerning management of ministry and the most important is the commitment to implement the process of students' ministry.Keywords: management of ministry, students ministry, fellowship, cell group